Transforming Society Through Zakat: Economic Empowerment, Poverty Alleviation, and SDGs Achievement in Indonesia –a Case Study of Baitul Maal Hidayatullah (BMH) - Halik, Abdul Chadjib; Jamaluddin Madjid; Amiruddin K (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study examines the impact of zakat programs managed by the National Amil Zakat Institution Baitul Maal Hidayatullah (BMH) on achieving the Sustainable Development Goals (SDGs) in Indonesia. Using a qualitative approach involving in-depth interviews, participatory observation, and document analysis, the research found that BMH's zakat programs significantly contribute to poverty alleviation (SDG 1), enhancing access to quality education (SDG 4), empowering community economies (SDG 8), and reducing social and economic inequalities (SDG 10). Zakat funds are utilized to meet basic needs, provide educational scholarships, and support micro-enterprises, collectively improving the welfare and self-reliance of zakat recipients. These findings reinforce the theory that zakat can serve as a social safety net and economic development catalyst, highlighting the importance of transparency and accountability in zakat management. However, this study is limited by a small sample size and subjective data from interviews. Future research should adopt a broader sample, integrate quantitative and qualitative methods, and explore other zakat programs. These findings have profound practical and policy implications, supporting zakat programs as strategic tools in national development and achieving the SDGs in Indonesia